Homologous pairing in genetic recombination: complexes of recA protein and DNA. - Shibata, T (1979)
recA protein, which is essential for general genetic recombination in Escherichia coli, promotes the homologous pairing of single-stranded DNA with double-stranded DNA to form a D loop. The amount of recA protein required for the reaction was directly proportional to the amount of single stranded DNA and was unaffected by similar variations in the amount of double-stranded DNA. The ATP analog, adenosine 5'-O-(3-thiotriphosphate) (ATP gamma S), which was not rapidly hydrolyzed by recA protein, blocked the formation of D loops but promoted the formation of stable complexes of recA protein and single-stranded DNA. These complexes, in turn, bound homologous or heterologous double-stranded DNA and partially unwound it. Because ATP gamma S competitively inhibited the ATPase activity of recA protein (Km/Ki approximately 300), we infer that ATP gamma S binds at a site that overlaps the site for ATP and that the functional complexes formed in the presence of the analog probably represent partial steps in the overall reaction. If the complexes formed in the presence of ATP gamma S reflect natural intermediates in the formation of D loops, recA protein must promote homologous pairing either by moving juxtaposed single-stranded and double-stranded DNA relative to one another or by forming and dissociating complexes reiteratively until a homologous match occurs.